2017
DOI: 10.1002/jcb.26019
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes as a Putative Tool to Investigate NAADP Signaling in Vasculogenesis

Abstract: Nicotinic acid adenine dinucleotide phosphate (NAADP) is the newest discovered intracellular second messengers, which is able to release Ca stored within endolysosomal (EL) vesicles. NAADP-induced Ca signals mediate a growing number of cellular functions, ranging from proliferation to muscle contraction and differentiation. Recently, NAADP has recently been shown to regulate angiogenesis by promoting endothelial cell growth. It is, however, still unknown whether NAADP stimulates proliferation also in endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…Accordingly, nicotinic acid adenine dinucleotide phosphate (NAADP) has been recently shown to underpin VEGF-induced endothelial Ca 2+ signals and neo-angiogenesis in melanoma [ 67 ]. An NAADP-sensitive lysosomal Ca 2+ store is also present in N-ECFCs [ 30 , 68 ], although it is seemingly down-regulated in BC-ECFCs (unpublished observations from our group).…”
Section: Discussionmentioning
confidence: 95%
“…Accordingly, nicotinic acid adenine dinucleotide phosphate (NAADP) has been recently shown to underpin VEGF-induced endothelial Ca 2+ signals and neo-angiogenesis in melanoma [ 67 ]. An NAADP-sensitive lysosomal Ca 2+ store is also present in N-ECFCs [ 30 , 68 ], although it is seemingly down-regulated in BC-ECFCs (unpublished observations from our group).…”
Section: Discussionmentioning
confidence: 95%
“…Likewise, PB‐ECFCs do not possess RyRs (Zuccolo, Dragoni, et al, ), which are also present in mature endothelial cells (Long, Cook, Wu, & Mitchell, ; Zhang et al, ). Finally, PB‐ECFCs display a remarkable acidic Ca 2+ store that can be liberated by NAADP‐gated TPC1 channels (Di Nezza et al, ; Zuccolo, Dragoni, et al, ). In terms of pro‐angiogenic Ca 2+ signals, TRPV4, albeit functionally expressed, exerts only a weak proliferative action on PB‐ECFCs (Dragoni, Guerra, et al, ), in marked contrast with its established role in arterial remodeling (Troidl et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…While the role played by InsP 3 Rs has been clearly established, it is still unknown whether NAADP‐gated TPC1 contributes to the onset of the Ca 2+ response to VEGF, as recently observed in HUVECs (Favia et al, , ). It is, however, intriguing that intracellularly delivered NAADP stimulates ECFC proliferation in a TPC‐dependent manner (Di Nezza et al, ). Parallel work from Prof. Beech's group confirmed that the genetic silencing of Stim1 and Orai1 prevent VEGF‐evoked Ca 2+ inflow in PB‐ECFCs, whereas VEGF promotes Stim1 relocation into sub‐membranal puncta (Li et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…NAADP-induced EL Ca 2+ release is, in turn, amplified by juxtaposed ER-embedded InsP 3 Rs and RyRs through the CICR process, thereby initiating a regenerative Ca 2+ wave [ 196 , 200 , 201 ]. NAADP-gated TPC2 channels are also expressed in vascular ECs [ 202 , 203 ], whereas N- ECFCs display larger amounts of TPC1 [ 86 , 204 ]. A recent study demonstrated that NAADP-induced Ca 2+ signals promoted tumor vascularization and metastasis in murine models xenografted with B16 melanoma cells [ 205 ].…”
Section: Enhanced Neovascularizationmentioning
confidence: 99%